2020
DOI: 10.3390/w12010182
|View full text |Cite
|
Sign up to set email alerts
|

Small and Medium-Scale River Flood Controls in Highly Urbanized Areas: A Whole Region Perspective

Abstract: While rapid urbanization promotes social and economic development, it poses a serious threat to the health of rivers, especially the small and medium-scale rivers. Flood control for small and medium-scale rivers in highly urbanized areas is particularly important. The purpose of this study is to explore the most effective flood control strategy for small and medium-scale rivers in highly urbanized areas. MIKE 11 and MIKE 21 were coupled with MIKE FLOOD model to simulate flooding with the flood control standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The early warning and post-assessment of extreme hydrological events are crucial for hazard mitigation. In [13], the authors explore the most effective flood control strategy for small and medium-scale rivers in highly urbanized areas. The probable cost-effective flood control scheme is to construct two new tributaries for transferring floodwater in the midstream and downstream of the Shegong river into the downstream of the Tieshan river.…”
Section: Summary Of the Papers In The Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The early warning and post-assessment of extreme hydrological events are crucial for hazard mitigation. In [13], the authors explore the most effective flood control strategy for small and medium-scale rivers in highly urbanized areas. The probable cost-effective flood control scheme is to construct two new tributaries for transferring floodwater in the midstream and downstream of the Shegong river into the downstream of the Tieshan river.…”
Section: Summary Of the Papers In The Special Issuementioning
confidence: 99%
“…Multidisciplinary research and advanced methodologies in hydrological forecasts, especially in extreme floods and droughts, are widely implemented for water planning and management, which ultimately lead to improved optimum water resources management and effective control under a changing environment. Among them, artificial intelligence (AI) techniques are efficient tools for extracting the key information from complex highly dimensional input-output patterns and are widely used to tackle various hydrological problems such as flood forecasts discussed in this Special Issue [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Over the last decades, many studies have demonstrated that artificial intelligence (AI) techniques, such as machine learning (ML) methods, can produce flood forecasts in a few hours [15][16][17][18][19] while extending to seasonal forecasts many months in advance for larger river basins [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Today, urban inundation models are widely used for studying urban inundation [ 15 ]. Scholars have developed many urban inundation models, including SSCM (Urban Storm Pipeline Calculation Model) [ 16 ], CSYJM (Urban Storm Runoff Model) [ 17 ], SWMM (Storm Water Management Model) [ 18 ], InfoWorks ICM (InfoWorks Integrated Catchment Management) [ 19 , 20 ], and MIKE series [ 21 , 22 ]. Models such as SSCM and CSYJM lack good pre- and post-processing programs, and most of them are based on applying research in a specific region [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the normalization of the side ditch depends on the type of road beside the side ditch, cross sectional channel type, and comparison between the depth and width of the channel [7,8]. The average rainfall intensity in the watershed area will be used as input data in the surface runoff discharge analysis [9][10][11]. The runoff coefficient will be derived from satellite imagery data [12,13], and the physical characteristics of the watershed area will be analyzed using the topographic map generated by the geographic information system (GIS) [14,15].…”
mentioning
confidence: 99%